Analysis of scenarios for transforming the object "Ukryttya" into an environmentally safe system by the method of multicriteria optimization - I. S. Skiter; V. V. Derenhovskyi (Ядерна фізика та енергетика)
Based on the criteria for comparative analysis of scenarios grouped into factors, the value of scenarios was determined using the multicriteria optimization methodology. The evaluation methodology includes indicators of weights of factor groups and weights of criteria for the relevant factors. Scenario value assessment is determined by calculating a generalized weighted additive function. It is used to rank the scenarios with the established parametric characteristics of the criteria. The results of the scenario assessment and their ranking are recommendations for making decisions on the sequence of scenario implementation.